Current Research Progress on Long Noncoding RNAs Associated with Hepatocellular Carcinoma - Haihong Shi; Yuxin Xu; Xin Yi; Dandan Fang; Xia Hou (Analytical Cellular Pathology)
Hepatocellular carcinoma (HCC) is the second leading cause of mortality among cancers. It has been found that long noncoding RNAs (lncRNAs) are involved in many human cancers, including liver cancer. It has been identified that carcinogenic and tumor-suppressing lncRNAs are associated with complex processes in liver cancer. These lncRNAs may participate in a variety of pathological and biological activities, such as cell proliferation, apoptosis, invasion, and metastasis. Here, we review the regulation and function of lncRNA in liver cancer and evaluate the potential of lncRNA as a new goal for liver cancer.